Respon tanaman selada (Lactuca sativa L.) terhadap kombinasi pemberian pupuk organik cair bahan daun gamal dan 50% NPK di tanah organosol - Arnayulis; Indah Larasati Hasibuan; Fedri Ibnusina (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Lettuce plants (Lactuca sativa L.) are a type of vegetable with high economic value. The community widely consumes them due to their many health benefits and ease of cultivation. This study aimed to determine the effect of the combination of liquid organic fertilizer (LOF) from gamal leaves + 50% NPK on the growth and production of lettuce as a substitute for 100% NPK fertilizer. The research was conducted at the State Agricultural Polytechnic of Payakumbuh from February to May 2025 using a Randomized Block Design (RBD) with four nutrient treatments: 100% NPK, 70 ml LOF/litre of water + 50% NPK, 100 ml LOF/litre of water + 50% NPK, and 130 ml LOF/litre of water + 50% NPK. Each treatment was repeated six times, resulting in 24 experimental units. The data obtained were analized with one-way ANOVA and further tested using Duncan's Multiple Range Test (DMRT). The results showed that the provision of nutrients has a significant effect (p<0,05) on the fresh weight of leaves, canopy weight, root weight, and root length, but does not have a significant effect (p>0,05) on leaf width and length. It can be concluded that the use of 70 ml LOF/litre of water + 50% NPK has proven to be very effective in replacing 100% NPK, and can improve soil quality, supporting a sustainable agricultural system.